MAPPING OF RESTAURANT DISTRIBUTION IN THE WONOKROMO DISTRICT AREA USING GOOGLE PLATFORM - Rifqi Hanan Riokka; Siti Zainab (CI-TECH, 2021)
Geographic Information System (GIS) or Geographic Information System (GIS) is a technology that is a tool and is essential for storing, manipulating, analyzing, and displaying natural conditions and often functions as a way to map an area with the help of data. attribute and spatial. The city of Surabaya is one of the big cities in Indonesia with a population of around 2,874,314 people in 2020. With a population of 2,874,314 people, many Surabaya residents meet their daily needs by trading, one of which is by opening a restaurant or depot. restaurant. There are so many restaurants or restaurant depots scattered in the city of Surabaya, as time goes on, there are more restaurants or restaurant depots and there are also more flavors, special foods, and so on. On this occasion, I tried to map several restaurants or restaurant depots in the city of Surabaya, one of which is in the Wonokromo sub-district. In this research, I use an application that is very easy to use in creating a path map that will usually be connected frequently to track the path from a certain point. The application is Google My Maps, the application will be used to create a path from the starting point to the end point. The purpose of this research is to help someone to find out the location of restaurant points or restaurant depots that are rarely known in the Wonokromo sub-district.